Bioactivity evaluation and HPLC UV-VIS based quantification of antioxidant secondary metabolites from extract and fractions of Bistorta amplexicaulis rhizome - Tabassam, Shahzadi; Anwar, Muhammad Asad; Gulfraz, Muhammas; Arshad, Muhammad; Sabitaliyevich, Uteuliyev Yerzhan; Nurmurzayevich, Sadykov Bolat; Ahmad, Muhammad Sheeraz (Cellular and Molecular Biology, 2019)
Bistorta amplexicaulis is a popular medicinal plant and reported as rich source of antioxidant compounds. The present study was designed for antioxidant and anticancer potential of polarity based fractions of B. amplexicaulis and its correlation to the secondary metabolites quantified by HPLC-UV/VIS.Crude extract was prepared by maceration method and polarity based fractions were prepared by solvent-solvent extraction. Antioxidant and anticancer potential was investigated by using various physiological and non-physiological assays while secondary metabolites rutin, naringin and quercetin present in extract and fractions were quantified by using HPLC- UV/VIS. All extracts showed Antioxidant potential but highest activity was obtained with ethyl acetate fraction (DPPH IC50 5.76±0.03 µg/ml, ABTS IC50 0.74±0.1 µg/ml, Total Antioxidant Assay 72.55±0.098 Ascorbic acid equivalents, Super oxide radical scavenging assay IC506.86±0.1909 µg/ml, Hydroxyl radical scavenging assay IC50 0.96±0.1690 µg/ml). The cytotoxicity of fractions against HepG2 cell lines showed lowest ell viability in n-hexane fraction (11%). The results revealed that ethyl acetate fraction of B. amplexicaulis can be a potential source of novel antioxidant compounds while n hexane fraction could provide anticancer compounds. A new method of simultaneous quantification of three flavonoids by using UV/VIS detector is reported in this study.